Evaluation of CEFE entrepreneurship training programmes in Asia / Dennis Ray … [et al.] (Faculty of Business and Management ; UiTM Press, 1996)
This paper explores the issues of evaluating entrepreneurship training programmes. Should entrepreneurship training programmes be evaluated?How?By whom? This paper focuses on a single major programme, that of CEFE/Technonet Asia financed by GTZ, the German economic development agency. Various methods of evaluation will be illustrated using data from four training programmes covering Nepal, Sri Langka, Bangladesh and Indonesia. In the process, issues involved in programme evaluation will be raised and discussed. This paper describes and evaluates one of the first maj or attempts to rely on action learning for entrepreneurship development in developing countries. Most training programmes in developing countries focus on the personality traits of prospective entrepreneurs. The CEFE model is not only a matter of interest to development agencies and entrepreneurs in Asia, Africa and Latin America, it has relevance to poverty reduction and entrepreneurship training in developed countries. The development of a science of entrepreneurship training and education depends on developing methodologies that critically and, to the fullest extent possible, independently assess entrepreneurship programmes and training activity.